Effect of Moisture Conservation Measures on Runoff, Soil Loss and Yield of Upland Rice - Panigrahi, B (Journal of Agricultural Engineering, 2007)
Field experiments were conducted during 2002 and 2003 in light textured eroded sloping land to study the effect of moisture conservation measures on runoff, soil loss and yield of upland rainfed rice in Balijorenala watershed, Orissa. Total six treatments i.e. (i) T1- fallow without any crop and conservation measures (control), (ii) T2 - crops grown without any conservation measures, (iii) T3 - vetiver grass planted in paired rows, (iv) T4 miniature bund with vetiver grass, (v) T5 - miniature bund with natural grass and (vi) T6 - V-ditch with vetiver grass were taken for the study. The treatment T6 was found to be superior to other treatments since it produced lowest average seasonal runoff and soil loss of 18.2% and 1.71 t/ha, respectively. On the other hand, the treatment T1 was observed to generate highest amount of average seasonal runoff and soil loss with values of 28.0% and 6.13t/ha, respectively. The yield of rice was found to be maximum with treatment T6 with a mean value of 19.1 q/ha whereas that for treatment T2, it was the lowest (13.1 q/ha). Thus, there was 45.8% increase in rice yield due to the maximum utilization of stored soil moisture in treatment T6 compared to treatment T2. Considering the effectiveness in reducing runoff, soil loss and enhancing the crop yield, treatment T6 is recommended as the best in-situ moisture conservation measures for rainfed upland farming system in sloppy land of Orissa.